2019
DOI: 10.1002/rcm.8533
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of aporphine alkaloids by electrospray ionization tandem mass spectrometry and density functional theory calculations

Abstract: Rationale Aporphine alkaloids represent a large group of isoquinoline natural products with important roles in biological and biomedical areas. Their characterization by electrospray ionization tandem mass spectrometry (ESI‐MS/MS) can contribute to their rapid identification in complex biological matrices. Methods We report the fragmentation of protonated 7,7‐dimethylaporphine alkaloids by ESI‐MS/MS, and the putative annotation of aporphine alkaloids in plant extracts. We used low‐ and high‐resolution MS/MS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The CH 3 O • elimination from C 6 H 9 NO +• resulted in C 5 H 6 N + formation at m/z 80.05016 (99%) (Figure 4B). A double successive elimination of radicals was previously observed in aporphine alkaloids by ESI(+)‐MS, and the product ion structures were studied by computational methods [44]. The mass spectra of macronecine, 7‐hydroxy‐1‐methylene‐8‐pyrrolizidine, laburnine, supinidine [45], macronecine N ‐oxide, and 7‐hydroxy‐1‐methylene‐8‐pyrrolizidine N ‐oxide revealed product ions and neutral losses similar to those observed for retronecine or its N ‐oxide.…”
Section: Resultsmentioning
confidence: 99%
“…The CH 3 O • elimination from C 6 H 9 NO +• resulted in C 5 H 6 N + formation at m/z 80.05016 (99%) (Figure 4B). A double successive elimination of radicals was previously observed in aporphine alkaloids by ESI(+)‐MS, and the product ion structures were studied by computational methods [44]. The mass spectra of macronecine, 7‐hydroxy‐1‐methylene‐8‐pyrrolizidine, laburnine, supinidine [45], macronecine N ‐oxide, and 7‐hydroxy‐1‐methylene‐8‐pyrrolizidine N ‐oxide revealed product ions and neutral losses similar to those observed for retronecine or its N ‐oxide.…”
Section: Resultsmentioning
confidence: 99%
“…For example, aporphine alkaloids are a group of isoquinoline-based alkaloids, and many of them show potential bioactivities, such as anti-diabetic, anti-oxidant, and anti-HIV activities [ 167 ]. A recent study using ESI-MS/MS and DFT calculations demonstrated the localization of the methylenedioxy, aromatic methoxy, vicinal methoxy, and hydroxy groups in 10 different 7,7-dimethylaporphine alkaloids, thus proving the ability of this method to quickly structurally characterize aporphine alkaloids [ 168 ].…”
Section: Applications Of Mass Spectrometry-based Techniques For Struc...mentioning
confidence: 99%
“…This may shed light on characterizing other epimeric saponins in future studies and facilitate the characterization and identification of the metabolites of epimeric saponins in both in vivo and in vitro experiments. However, the mechanism of the stereospecific fragmentations of epimers does need further study, in which the isotope‐labelled method and density functional theory or quantum chemistry calculations may play a key role.…”
Section: Lc/dad‐it‐tof‐ms Analysis Of Saikosaponins C a D B1 And Bmentioning
confidence: 99%